2019
DOI: 10.1016/j.athoracsur.2018.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Electric Shock–Induced Coronary Artery Thrombosis and Dissection

Abstract: Electric shock-induced myocardial infarction is rare. Shock-induced coronary artery thrombosis and dissection in multiple distributions have not been reported. After shock, coronary thrombosis may cause anginal symptoms, and any coronary artery may be damaged. A 32-year-old man presented with angina and ischemia-related symptoms post 6,000-V electric shock. He reported occasional exertional angina; stress echocardiography was positive for ischemia. Catheterization showed severe multivessel disease, occluded le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…Electric shock–induced injuries are rarely reported. To our knowledge, the only previously reported cases of cardiac damage are from Akci et al, who reported a case of myocardial infarction after electric shock, and from Jacob and Belli at our institution, who reported a case of electric shock–induced coronary artery thrombosis and dissection requiring coronary artery bypass grafting (case 1 in this series). The ideal treatment for coronary damage from electrical shock is not known.…”
Section: Discussionmentioning
confidence: 60%
“…Electric shock–induced injuries are rarely reported. To our knowledge, the only previously reported cases of cardiac damage are from Akci et al, who reported a case of myocardial infarction after electric shock, and from Jacob and Belli at our institution, who reported a case of electric shock–induced coronary artery thrombosis and dissection requiring coronary artery bypass grafting (case 1 in this series). The ideal treatment for coronary damage from electrical shock is not known.…”
Section: Discussionmentioning
confidence: 60%
“…Electrical injury can be fatal owing to complications such as ventricular fibrillation or coronary artery thrombosis and dissection. 5 Guidelines recommend 12-lead electrocardiography and 24-h monitoring after an electrical injury if the patient has any risk factors for arrhythmias. 6 Their necessity and the duration of cardiac monitoring are topics of debate.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism for massive coronary artery thrombosis and dissection was not understood. 14 Vascular damage occurs more in the media, possibly because of the blood flow diffusion of heat away from the intima. Intimal damage may result in either immediate or delayed thrombosis or vascular occlusion as edema and clots form on the damaged internal surface of vessels.…”
Section: Autopsy Findingsmentioning
confidence: 99%